Gas6/AXL signaling contributes to GnRH-dependent activation of pituitary gonadotropes - Mohammad Zadeh, Pardis, author; Amberg, Gregory C., advisor; Hoerndli, Frederic, committee member; Stasevich, Timothy, committee member; Winger, Quinton, committee member (Colorado State University. Libraries, 2023)
Gonadotropin-releasing hormone (GnRH) receptor plays a fundamental role in reproduction and is prevalent in various urogenital, reproductive, and non-reproductive cancers. Beyond the conventional G protein-coupled receptor signaling, GnRH receptors interact functionally with multiple receptor tyrosine kinases. AXL, a receptor tyrosine kinase found in various tissues and numerous tumors, is the focus of this dissertation to discover its impact, along with its endogenous ligand Gas6, on GnRH receptor signaling. In this study, clonal murine pituitary αT3-1 and LβT2 gonadotrope cell lines were utilized to evaluate the effect of AXL activation on GnRH receptor-dependent signaling pathways. A combination of ELISA and immunofluorescence techniques was employed to analyze AXL and GnRH receptor expression in αT3-1 and LβT2 cells, as well as in murine and human pituitary sections. Additionally, ELISA was used to quantify alterations in ERK phosphorylation, pro-MMP9 production, and the release of LHβ. The abundance of Egr-1 transcripts was measured using digital droplet PCR. To assess αT3-1 and LβT2 cell migration responses to GnRH and AXL, trans-well migration assay was used. Results showed the presence of AXL, alongside GnRH receptors, in αT3-1 and LβT2 gonadotrope cell lines, as well as in murine and human pituitary sections. In line with AXL's potentiating role, Gas6 enhanced GnRH-dependent ERK phosphorylation in αT3-1 and LβT2 cells. Furthermore, Gas6 increased the abundance of Egr-1 transcripts, suggesting enhanced post-transcriptional GnRH receptor responses. Notably, in LβT2 cells, Gas6/AXL signaling not only stimulated LHβ production but also enhanced GnRH receptor dependent pro-MMP9 protein generation and promoted cell migration, underlining its functional significance. In summary, our findings unveil a hitherto undiscovered role for AXL as a modulator of GnRH receptor signaling.
Keywords: GnRH receptor; molecular endocrinology; signal transduction; GPCR; AXL receptor; RTK